Comparative Analysis Of Vehicle Operating Cost (BOK) Using the Pacific Consultant International (PCI) Method On The Kaliwungu – Krapyak Toll Road and Non-Tol Road - Yuliasih, Larasati Welas; Sari, Putri Ameliya; Wardani, Agustina; Yudaningrum, Farida (Science and Technology Research Centre, Universitas PGRI Semarang, 2026)
The Kaliwungu–Krapyak Toll Road is one of the road sections that connects Kendal Regency and Semarang City and is part of the Trans Java Toll Road network. Differences in traffic conditions and road characteristics between toll roads and non-toll roads can affect the magnitude of Vehicle Operating Costs (VOC) incurred by road users. This study aims to identify the variables that influence Vehicle Operating Costs (VOC) and to analyze the VOC values on the Kaliwungu–Krapyak Toll Road and the Kaliwungu–Krapyak Non-Toll Road using the Pacific Consultant International (PCI) method. The research data were obtained through the collection of primary and secondary data related to vehicle operating cost variables, including fuel consumption, lubricant usage, vehicle maintenance costs, tire wear, vehicle depreciation, capital interest, insurance costs, and unexpected costs. The results show that the VOC value is influenced by vehicle speed and traffic conditions on each road segment. The lowest VOC value on the Kaliwungu–Krapyak Toll Road occurs at a speed of 70 km/h, while on the Kaliwungu–Krapyak Non-Toll Road it occurs at a speed of 57 km/h. Based on these results, the analysis of VOC variables can be used to describe the efficiency of vehicle operating costs on both road sections.